2006
DOI: 10.1210/jc.2006-0461
|View full text |Cite
|
Sign up to set email alerts
|

Salivary α-Amylase Levels after Yohimbine Challenge in Healthy Men

Abstract: The results indicate that yohimbine administration activates not only autonomic parameters but also sAA via adrenergic mechanisms, suggesting that sAA might be an indirect indicator of the central sympathetic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(107 citation statements)
references
References 13 publications
6
93
1
4
Order By: Relevance
“…Our results may, therefore, indicate increased sympathetic activity during the amniocentesis, but further research is needed. These findings parallel previous results from our workgroup on nonpregnant healthy participants (27,45) and are in line with our prior study on sAA reactivity during pregnancy revealing an increase in second-and third-trimester pregnant women confronted with an acute laboratory-based psychosocial stressor (42).…”
Section: Discussionsupporting
confidence: 92%
“…Our results may, therefore, indicate increased sympathetic activity during the amniocentesis, but further research is needed. These findings parallel previous results from our workgroup on nonpregnant healthy participants (27,45) and are in line with our prior study on sAA reactivity during pregnancy revealing an increase in second-and third-trimester pregnant women confronted with an acute laboratory-based psychosocial stressor (42).…”
Section: Discussionsupporting
confidence: 92%
“…Direct measurements of salivary adrenaline and noradrenaline seem not to reflect SAM activity (Schwab et al 1992). However, salivary alpha-amylase (sAA) appears as a promising marker, as non-invasive and easily obtainable (Nater et al 2005;Granger et al 2007) since Ehlert et al (2006) provided evidence through pharmacological manipulation of the SAM system. In fact, these authors showed that yohimbine administration activates not only autonomic parameters but also sAA via adrenergic mechanisms, suggesting that sAA might be an indirect indicator of the central sympathetic system.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that low morning levels of sAA could have a role as a possible risk factor. To explain these findings, some researchers have speculated that sAA activity could be a potential surrogate marker for the level of noradrenaline in the central nervous system (CNS) (Buchanan, Bilbas, & Adolphs, 2010;Ehlert, Erni, Hebisch, & Nater, 2006;Rohleder, Nater, Wolf, Ehlert, & Kirschbaum, 2004;Sanchez-Navarro et al, 2012;Van Stegeren et al, 2006). Other recent studies have reported that this association between sAA and peripheral noradrenaline is statistically significant when it is measured in healthy subjects confronted by psychosocial laboratory stressors (Ditzen, Ehlert, & Nater, 2014).…”
Section: Discussionmentioning
confidence: 99%